Implementasi IoT Pada Sistem Pembayaran di Koperasi Sekolah - Mesri Silalahi; Saut Pintubipar Saragih (LPPM Universitas Putera Batam, 2023)
Information technology has been widely adopted by numerous educational institutions, both formal and informal, based on religion or non-religious, The urgency of innovative technologi which appliable to school business processes are rising rapidly within enormous applicable internet of Things available. The research methodology in this research conducted comprehensively. Researcher will used the technolgu of Microcontroller Esp32 to help the implementation of payment in one of the department of the research object. Developing the system within the school system will need very trmendous effort to justify the system accepted by all the stakeholder. Researcher using the srum methods in software development and using the esp32 microcontroller as the thechologu to merged within, researcher hope the capablity of Background Subtraction Algorithm on ESP32, it is elucidated that the background subtraction algorithm can be implemented on the ESP32 device. This device possesses the capability to process image frames measuring 80 x 60 pixels a total of 10,000 times within a temporal span of 2,000 milliseconds (at an approximate rate of ±5,000 frames per secondThe result of this research supposedly achieve the implementation of the microcontroller technology to provide the solution in school business unit payment processes. All the visitor to the business unit are detected with the RFID card using the microcontroller to automate the identification and enabling better transaction process flow.